Estágio supervisionado no Ensino Fundamental anos iniciais: uma práxis epistemológica na formação do professor (a) - SILVA, Josilene Santos da (2024)
The purpose of this article is to discuss the activities of Supervised Internship in Elementary School Early Years, in the Municipality of Bragança/PA. This Internship took place from (05) the fifth to (20) the twentieth of September 2023, at EMEIF Simpliciano Fernandes de Medeiros Júnior, in a 3rd year class. It is worth highlighting that, from the Practice/Internship actions to the preparation of this article, a qualitative approach was adopted, understanding the need to be categorical in collecting and understanding data, as well as in delving deeper into the proposed theme. This research presents itself as descriptive and explanatory. For Silva & Menezes (2000, p.21), descriptive research seeks to point out the characteristics of the reality of a given population and any phenomenon/fact that instigates interest or demands a problem to be investigated and understood. To classify this study, it was also decided to carry out a questionnaire to be answered by the teacher in charge of the internship classroom, understanding that, as presented by Lakatos and Marconi (2002, p.201), the questionnaire “[.. .] is a data collection instrument, consisting of an ordered series of questions, which must be answered in writing, and without the presence of the interviewer.” Therefore, this article aims to discuss the internship activities and the theoretical knowledge learned during the pedagogy course, in order to understand and/or reflect on how the internship school sees this training phase, but also to understand which the role of the internship for the intern and the classroom teacher. However, it was clear from the observation and intervention phase, as well as the theoretical studies undertaken and the speech of the teacher leading the class where the internship/research took place, that there is a need for the school, specifically the teacher, to review their knowledge/ teaching activities, seeking to improve their pedagogical practice in continued training and also theoretical studies, in order to develop pedagogical practices and strategies that focus on the student's cognitive, intellectual and human development, developing knowledge/practices that enable the construction of strategies with based on the epistemological construction of praxis.